Optimized trapezoidal-shaped hip implant for total hip arthroplasty using finite element analysis. Issue 1 (1st January 2020) - K N, Chethan; Zuber, Mohammad; Bhat N, Shyamasunder; Shenoy B, Satish
Abstract: Hip implants consist of a stem, femoral head, acetabular cup, and backing cup. There is a wide variety of sizes and lengths. Their adaptability is limited because of the inter-anatomical variations. There is no single fit-for-all implant design that satisfies the orthopedic requirement satisfactorily. In this work, the trapezoidal-shaped stem with three different cross-sections is considered. The femoral head size, acetabular cup thickness, backing cup thickness, and trunnion geometry were varied to arrive at the best possible combination. ANSYS R-19 was used to perform the static analysis. It is found that trapezoidal-shaped profile two has the least amount of stress and total deformation. The von Mises stresses were found to be higher when the femoral head size was between 32 mm to 40 mm in profile two. It was also observed that the femoral head with 24 mm has the least stress compared to higher head sizes. The maximum von Mises stress-induced in profile two was 141.0 MPa, the total deformation of 0.04436 mm and elastic strain of 7.6 × 10 −4  mm/mm. Trunnion interface does not have a significant role with respect to the structural strength of the implant. From the findings of this study, it is inferred that profile two shaped stems with the femoral ball size of 36 mm, acetabular cup thickness of 2 mm and backing cup thickness of 1mm is best suited for the hip replacement. The major outcome of this study is the utilization of the DoE method to determine the optimized value of the implant.